Economic evaluation of technology for a new generation biofuel production using wastes. (January 2016) - Koutinas, Athanasios; Kanellaki, Maria; Bekatorou, Argyro; Kandylis, Panagiotis; Pissaridi, Katerina; Dima, Agapi; Boura, Konstantina; Lappa, Katerina; Tsafrakidou, Panagiota; Stergiou, Panagiota-Yiolanda; Foukis, Athanasios; Gkini, Olga A.; et al.
Highlights: Economic evaluation of new generation biofuel production using wastes. A preliminary investment and cost analysis of the proposed technology is presented. The process is based on scale-up results of waste acidogenesis. Extraction of the produced organic acids was done with butanol-1. Abstract: An economic evaluation of an integrated technology for industrial scale new generation biofuel production using whey, vinasse, and lignocellulosic biomass as raw materials is reported. Anaerobic packed-bed bioreactors were used for organic acids production using initially synthetic media and then wastes. Butyric, lactic and acetic acid were predominately produced from vinasse, whey, and cellulose, respectively. Mass balance was calculated for a 16, 000 L daily production capacity. Liquid–liquid extraction was applied for recovery of the organic acids using butanol-1 as an effective extraction solvent which serves also as the alcohol for the subsequent enzyme-catalyzed esterification. The investment needed for the installation of the factory was estimated to about 1.7 million € with depreciation excepted at about 3 months. For cellulosics, the installation investment was estimated to be about 7-fold higher with depreciation at about 1.5 years. The proposed technology is an alternative trend in biofuel production.